PERSUASIVE PUBLIC RELATION COMMUNICATION STRATEGY OF UIN RADEN MAS SAID SURAKARTA AND UIN SAIFUDDIN ZUHRI IN SOCIAL MEDIA FOR INCREASING THE IMAGE OF HIGHER EDUCATION - Fathan; Toto Suharto; Abdul Matin Bin Salman (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
Image is an important element for the institution as a reflection of the institution's quality in the eyes of the community. Part of the institution that functions to form an image is public relations (PR). This study aims to explain the role of public relations in improving the image of Islamic universities in Central Java. The two universities selected as research objects are UIN (Universitas Islam Negeri) Raden Mas Said Surakarta and UIN Saifuddin Zuhri Purwokerto. The two institutions transformed IAIN (Institut Agama Islam Negeri) into UIN in 2021. The research approach used was qualitative. This study resulted that the two universities functioned in public relations to improve the institution's image. In addition, public relations also performed as a means of da'wah, considering that both universities are Islamic religious colleges.